PENGEMBANGAN INSTRUMEN KEMITRAAN DESA SIAGA DI KABUPATEN SUBANG, JAWA BARAT - Kodrat Pramudho, Peristiwanto Adiyono (GIZI INDONESIA, 2009)
THE DEVELOPMENT OF PARTNERSHIP INSTRUMENT OF “DESA SIAGA” IN SUBANG DISTRICT, WEST JAVA PROVINCEThe successful of “Desa Siaga” as one of the forms of Community Based Health Activities (CBHA)depends on, among others, the good partnership of different elements in the community, especiallythe  partnership between  health  providers  with  the community.  Desa  Siaga is a  village that hasenough  human  resources,  abilities,  and  willingness  to  prevent  and  solve  any  health  problem,disasters and emergencies occurred in the village self reliantly. The objective of this study is todevelop the instrument that is able to measure the partnership of Desa Siaga in Indonesia. The studyis conducted in Subang District, since this district has been declared as the only district that has 100percent Desa Siaga in the whole district. The length of study is nine months, starting from February,2008.  The  method  of  study  is  a  mixed  paradigm,  which  is  a  combination  of  qualitative  andquantitative study methods. The methods of study used in the qualitative study are focus groupdiscussion (FGD), in-depth interview (IDI), and expert meeting. While in the quantitative study is across-sectional method. The result of this study were: Firstly, from the literature review it reveals thatthere are three main variables that are important in partnership, namely openness, equality andmutual benefit. Secondly, from FGD and IDI, these methods are able to elaborate three main variablesas mentioned above into 31 detailed variables. Thirdly, result from the expert meeting is the churnedout of the 31 detailed variables into 52 detailed variables. Fourthly, by using factor analysis of theopinions prompted from 172 respondents, we are able to subtract these 52 detailed variables into 17main variables that are the important to determine the degree of partnership of Desa Siaga. These 17main variables, then, are to be used as the main variables in the development of instrument tomeasure the degree of partnership of Desa Siaga. This instrument has been tested in 30 villages inSubang District. The results are: 17 villages with good partnerships and the remaining 13 with lesssatisfactory partnerships. If we cross-tabulate the result from the study, it reveals that villages whichfall into “good” categorization tend to have good partnership in Desa Siaga.